Assessment of Technical Efficiency and Its Determinants in Maize (Zea Mays) Farming System of Chitwan, Nepal - Sharma, Pratiksha (Nepalese Journal of Agricultural Sciences, 2025)
Maize is the second major staple crop of Nepal which is commonly used for human consumption and animal feed. This study analyzed technical efficiency and its determinants in Chitwan’s maize farming system. Two villages, Shaktikhor and Fulbari, were purposively selected for this study. In total, 120 maize-growing farmers were selected using simple random sampling, with 60 respondents from each site. Primary data were collected using a set of well-structured pretested questionnaire. The data obtained were analyzed using the stochastic production frontier and Tobit regression. The analysis revealed that the average maize productivity at the site was 1261.21 kg ha-1 and was significantly affected by tractor time, farmyard manure, and labor. Technical efficiency was found to vary from 16.7% to 89.7%, with an average of 64.5%. Household head’s age, household head’s education, access to credit, and extension/training were positive significant determinants of technical efficiency, and every unit increase in each of these variables found to increase technical efficiency by 0.002, 0.001, 0.126, and 0.071 unit, respectively. There is sufficient scope to increase technical efficiency with the same amount of inputs. The local and national governments should emphasize enhancing loans and credit facilities. Furthermore, more educated people should be motivated to be involved in maize farming, and extension or training programs should be boosted to expand maize production efficiency.